Avaliação em profundidade do Programa de Tratamento Fora de Domicílio (TFD): trajetórias dos usuários e as redes de acolhimento no serviço de transplante renal do Hospital Universitário Walter Cantídio - Carvalho, Maria de Fátima Sousa Lima de (2024)
The central purpose of this study is to evaluate the Treatment Out of Home Program (TFD) through the trajectories of users and their care networks served in the kidney transplant service of the Walter Cantídio University Hospital (HUWC), institution that is part of the Hospital Complex of the Federal University of Ceará, together with the Assis Chateaubriand Maternity School. Based on a counter-hegemonic perspective, the carrying out of this evaluative research was supported by the in-depth evaluation whose proposal Rodrigues (2008) agrees with is placed in a contextualized, dense, broad and multidimensional way, as it considers the political, social and human dimension of/ the subjects involved. That said, this research aimed to evaluate the guarantees provided by the Out-of-Home Treatment Program to users and their reception networks for kidney transplantation. In particular, an analysis of the context of implementation of the TFD Program was carried out; the evaluation of the content of Ordinance nº 055/SAS/MS that governs the TFD and its conceptual bases, such as the States' Out-of-Home Treatment Manual; in addition to understanding the experiences of TFD users, families and professionals through the following questions: What are the psychosocial impacts of the TFD routine for users? What is the role of the family in the treatment and care process? What role/function does TFD confer on the family? What is the perception of managers and health professionals about the Program? As a methodology, a qualitative approach was achieved, plus quantitative data and bibliographic and documentary analysis. Such as semi-structured interviews distributed among users, program managers and health professionals due to the need to incorporate the subjects' different interpretations of the policy and their trajectories in institutional spaces.